Superior simultaneous immobilization of cadmium and arsenic by ferrihydrite-modified biochar: performance and mechanisms - Teng, Xiaowen; Yang, Weizhong; Chen, Hanbo; Wu, Xuqiao; Tang, Jianing; Yang, Xiaohui; Liu, Zhenyu; Liu, Dan; Xu, Weijie (Frontiers in Environmental Science, 2026)
The contrasting geochemical behaviors of cationic cadmium (Cd) and anionic arsenic (As) in co-contaminated soil pose a significant challenges for their simultaneous immobilization. To address this issue, three materials were developed: pristine biochar (BC) derived from rice straw, pure ferrihydrite (FH), and ferrihydrite-engineered biochar (FB) produced through iron-oxide impregnation. These materials were applied to contaminated soil at 1.0%-3.0% (w/w) to evaluate their effects on soil properties and metalloid stabilization. The results showed that the FB treatment significantly improved soil pH, cation exchange capacity (CEC), electrical conductivity (EC), and organic matter (OM) content. Compared to control, the FB3% treatment produced the strongest effects after 120 days, increasing CEC and OM by 19.31% and 17.97%, respectively. Soil pH and EC also increased by 11.4% and 7.5% relative to the control. Moreover, FB3% treatment significantly reduced bioavailable Cd and As by 51.58% and 72.94%, outperforming BC and FH. The sequential extraction results indicated that FB promoted the transformation of Cd and As from exchangeable to residual fractions. After 120 days, exchangeable Cd and As decreased by 55.53% and 45.50% relative to the control. Material characterization revealed that ferrihydrite loading increased the Fe content, surface area of the biochar, and functional groups (-OH and C=O) of biochar. Overall, FB exhibited superior immobilization performance through electrostatic attraction, surface complexation, and co-precipitation, demonstrating its strong potential as an efficient amendment for remediating Cd/As co-contaminated soils.